Variable Gain PI Controller Design For Speed Control of a Doubly Fed Induction Motor Using State-Space Nonlinear Approach - Mohammed Chikouche, T.; Mezouar, A.; Terras, T.; Hadjeri, S. (Engineering, Technology & Applied Science Research, 2013)
This paper presents a comparison between a variable gain PI controller and a conventional PI controller used for speed control with an indirect field orientation control of a Doubly Fed Induction Motor (DFIM), fed by two PWM inverters with a separate DC bus link. By introducing a new approach for decoupling the motor’s currents in a rotating (d-q) frame, based on the state space input-output decoupling method, we obtain the same transfer function (1/s) for all four decoupled currents. Thereafter, and in order to improve control performance, the VGPI controller was used for speed regulation. The results obtained in Matlab/Simulink environment illustrate the effectiveness of the technique employed for the decoupling and for speed regulation.